Pengaruh Model Problem-Based Learning pada Pelajaran Sistem Instalasi Tata Udara - Purnama, Anang; Aswardi, Aswardi (Jurnal Pendidikan Teknik Elektro, 2024)
This research aims to assess the influence of a Problem-Based Learning model or method on student learning outcomes in the Air Conditioning Installation Systems subject at SMK Negeri 1 West Sumatra. The subjects of this research were class XII TPTU students consisting of 25 students. Low student scores can be influenced by the implementation of learning models that have not optimized students' active role in the learning process. Therefore, research was conducted that utilized the problem-based learning model as a strategy to achieve more effective learning, to increase student achievement of learning outcomes. The analysis techniques used in this research are students' classical learning completeness and effect size analysis. This type of research is pre-experimental (pre-experimental) with a One Group Pretest-Posttest design. Based on the results of the research carried out, it can be concluded that the use of the Problem-Based Learning model is very influential in class XII TPTU SMKN 1 West Sumatra. This can be seen from the average pretest score is 66.28 and the average posttest score is 84.8. The calculation of Cohen's effect size analysis is 2.03, which shows a large category since the Problem-Based Learning model was used, and by calculating the completeness of student learning outcomes on the post-test score, a percentage of 88% was obtained, exceeding the classical completeness criteria set at 85% on high success criteria. . Based on the data obtained, it can be concluded that the application of the problem-based learning model (Problem-Based Learning) has proven successful in improving the learning outcomes of class